Keefektivan Ekstrak Daun Sirih Hutan Sebagai Pengendali Serangan Hama Penggerek Buah Kopi (Hypothenemus hampei Ferrari) di Lapangan - Pardosi, John Agus Sahputra; Wibowo, Arif Ravi; Sibarani, Ebenezer Muaratama (Jurnal Agro Industri Perkebunan, 2024)
The coffee berry borer (CBB), caused by the Hypothenemus hampei Ferrari insect, is a significant pest for coffee farmers, particularly attacking the berries and affecting both the quality and quantity of coffee production. CBB attacks can reduce the quantity and quality of coffee plant production. CBB can be controlled by using botanical pesticides. One such botanical pesticide is derived from the Piper aduncum L. plant, which contains various compounds including dilapiol, piperamidin alkaloid, flavonoids, saponins, steroids, polyphenols, tannins, and terpenoids. This study aimed to test the effectiveness of botanical pesticides from P. aduncum L. in controlling CBB. This experiment used a non-factorial randomized block design (RBD) with one factor studied, namely the effect of variations in the provision of botanical pesticides of Piper aduncum L. with treatments P0 = control; P1 = 15%; P2 = 25%; P3 = 35%; and P4 = chemical pesticides. This experiment consisted of 5 treatment levels with three replications, each containing ten pests. The results showed that treatment P3 (35%) was the most effective concentration in controlling CBB. Botanical pesticides at a concentration of 35% had the same effect as chemical pesticides on the parameters of mortality observation and suppression of pest attack intensity.